ENHANCING LEARNING BEHAVIOR OF STUDENTS WITH DISABILIITES THROUGH PULL-OUT CLUSTER MODEL (POCM) (A CASE STUDY ON LEARNING PROBLEMS OF STUDENTS WITH DISABILITY IN INCLUSIVE SCHOOLS) - Gunarhadi Gunarhadi (Proceedings of The ICECRS, 2016)
Students with disabilities in inclusive schools are often hurdled in learning barriers, and differentiated instruction of Pull-out Cluster Model (POCM) is found to be a solution. This research aims at: (1) exploring the values of POCM. (2) measuring the effectof POCM on the learning behavior of students with disabilities in inclusive classroom. This research is a case study involving teachers and students in two different regular schools in Surakarta, Central Java, Indonesia. Data was collected from questionnaire and observation. Questionnaire was used to evaluate the lesson plan, while observation was used to describe the teacher’s activities and studens’ learning behavior during lesson study. The data was analyzed by both quantitative and qualitative descriptive of two different instructional models. The results showed that (1) POCM exceeded full inclusive model in term of lessson plan. (2) students with disabilities indicate better behavior of learning participation. This research suggests that inclusive schools provide POCM system that is adaptive to learning behavior of students with disabilities.